Efektifitas dan Efisiensi dalam Job Description Kepanitian Idul Adha Masjid Jogokariyan 1441 H - Mawehda, Mawehda; Rizky, M. (STID Al Hadid Surabaya, 2024)
Job Description Eid al-Adha Committee 1441 H Jogokariyan Mosque Abstrac: This research focuses on job descriptions in the Eid al-Adha 1441 H Jogokariyan Mosque committee. The aim of this research is to describe the authority and responsibility, conditions, standards and machines used in each job to make the implementation of the 1441 H Jogokariyan Mosque sacrifice a success. The method used in this research is library or literature study by collecting credible documents and references, then the analysis was carried out using Garry Dessler’s Job description theory approach. The results of the research show that the Eid al-Adha 1441H committee has 16 types of work including: Cow hunting team, animal slaughtering team, consumption team, first aid team, personnel & K3 team, media team, progress report & documentation, offal processing team, shohibul wrapping team, Bone cutting team, Meat weighing & cutting team, Cow & goat straddling team, Cow lifting team, Live cattle weighing team, Cow herding team, Cow & goat drumming team. Each team that is formed has a specific explanation of authority and responsibility according to the needs and conditions of the objective of completing the slaughter of 44 cows and 39 goats, effective and efficient work standards with the use of sophisticated machines so that all the meat is ready to be distributed at 12:10 from 08:00 :00, and the distribution process of 4,750 packs was completed before sunset on the same day. Keywords: Job description, Eid al-Adha committee, Jogokariyan Mosque